METODE JUST IN TIME DAN ALGORITMA WAGNER WITHIN DALAM PENGENDALIAN PERSEDIAAN ALAT KESEHATAN - Reka Rahmawi; Rina Filia Sari; Ana Uzla Batubara (LPPM Universitas Bina Bangsa, 2023)
Inventory control needs to be considered because it has a very important meaning in running the company’s business, such as in the medical device distributor company Prima Jayac Alkes. The problem discussed is only for sterile non-electromedical medical devices, namely Disposable 1cc, 3cc, 5cc, and 10cc. In this study, two methods of comparision of inventory control systems will be presented, namely calculating the total cost between the Just in Time (JIT) method and Wagner Within Algorithm. The purpose of this study is to perform a comparative analysis of the cost of medical equipment inventory using the Just in Time methods and the Wagner Within algorithm. Based on the calculation result result in the acquisition of total inventory costs, it shows that the Wagner Within Algorithm methods obtains lower costs compared to Just in Time and company’s actual system for Disposable Syringe 1cc and Disposable Syringe 5cc. Meanwhile, for Disposable Syringe 3cc and Disposable Syringe 10cc, the Just in Time Methods has a lower cost compared to Wagner Within Algorithm and Company’s actual system